PROTEIN LEVEL EFFICIENCY OF TILAPIA Oreochromis niloticus FEED WITH SELENOMETHIONINE SUPPLEMENTATION - Pattipeilohy, Christian Ernsz; Pattiasina, Bethsy Jane; Loupatty, Joice Welly; Pattirane, Chrisoetanto Patrick (Universitas Mataram, 2025)
One of the nutrients that play an important role for fish growth is protein, one of which is in the formation of body tissues. The amount and quality of protein in fish feed affects growth performance, feed utilization, water quality and of course the price of the feed itself. Excessive feed protein or whose quality does not meet the needs will be excreted as nitrogen waste, especially in the form of ammonia. This study aimed to reduce protein consumption in tilapia (Oreochromis niloticus) diets through selenomethionine supplementation. The test feed was designed using two different protein concentrations: 26% and 30%. Selenomethionine supplementation levels were 0 mg/kg (control) for 30% feed protein, and 3 mg/kg and 6 mg/kg Se for 26% feed protein. This study used a completely randomized design (CRD) with three treatments and three replicates. Tilapia with an average initial weight of 8.05 ± 0.25 g were reared in an aquarium measuring 100×50×50 cm³ with a stocking density of 15 fish per aquarium. The fish were reared for 60 days and fed three times a day until full. The results showed that supplementation of 3 mg/kg Selenomethionine to 26% feed protein was better than either the control or 6 mg/kg Se supplementation. Supplementation of 3 mg/kg Se to 26% feed protein level significantly increased feed intake (FI), final biomass weight (Bt), feed conversion ratio (FCR), feed efficiency (FE), protein retention (PR), and daily growth rate (DGR) in tilapia. A 100% survival rate was recorded in all treatment groups.